Odpowiedzi

Najlepsza Odpowiedź!
2010-03-16T23:20:06+01:00
A)
√2x+ 3y= 5 {obie strony mnożymy przez -√2}
{
2x- √2y= √2

-2x -3√2y = -5√2 {dodajemy stronami}
{
2x- √2y = √2

-4√2y = -4√2 /:(-4√2)
{
2x- √2y= √2

y = 1
{
2x- √2*1= √2

y=1
{
2x - √2 = √2 /+( √2)
y=1
{
2x = 2√2
y=1
{
x = √2
Odp. x = √2 i y = 1


b)
(√2-1)x + 3√2y= -√2 - 2
{
(√2+1)x + 3y= 2√2 + 5 /*(-√2) {obie strony mnożymy przez -√2}

(√2-1)x + 3√2y= -√2 - 2
{
(-√2)*(√2+1)x + 3*(-√2)y= (2√2 + 5)*(-√2)

(√2-1)x + 3√2y= -√2 - 2 {dodajemy stronami}
{
(-2 -√2)x - 3√2y= -4 - 5√2

(√2-1)x + (-2 -√2)x = -√2 - 2 -4 - 5√2
{
(√2+1)x + 3y= 2√2 + 5

x(√2-1-2 -√2) = -6 -6√2
{
(√2+1)x + 3y= 2√2 + 5

-3x = -6 -6√2 /:(-3)
{
(√2+1)x + 3y= 2√2 + 5

x = 2 + 2√2 {wstawiamy do drugiego równania}
{
(√2+1)x + 3y= 2√2 + 5

x = 2 + 2√2
{
(√2+1)*(2 + 2√2) + 3y= 2√2 + 5

x = 2 + 2√2
{
2√2+ 4 + 2 + 2√2 + 3y= 2√2 + 5

x = 2 + 2√2
{
3y= 2√2 + 5 - 2√2- 4 -2 - 2√2

x = 2 + 2√2
{
3y= -1 - 2√2 /:3

x = 2+ 2√2
{
y= ⁻⅓ - ⅔*√2

Odp. x= 2+ 2√2 i y= ⁻⅓ - ⅔*√2


c)
7x + 3y= 10¹⁴ /*(-2)
{
14x - 4y= 10¹⁴

-14x - 6y = -2*10¹⁴
{
14x - 4y= 10¹⁴

-10y = - 10¹⁴ /:(-10)
{
14x - 4y= 10¹⁴

y = 10¹³
{
14x - 4*10¹³ = 10¹⁴

y = 10¹³
{
14x = 10¹⁴ + 4*10¹³

y = 10¹³
{
14x = 14*10¹³ /:14

y = 10¹³
{
x = 10¹³
Odp. x = 10¹³ i y = 10¹³